Supporting the Identification of Natural Sounds in Ecoacoustic Soundscapes Through Spectrogram-Based Analysis Methods - Popp, Jana; Edler, Bernd; Popel, Cornelius (IEEE 5th International Symposium on the Internet of Sounds, IS2 2024, 2024)
As a contribution to addressing the challenges posed by climate change, acoustic ecology, and in particular the study of changes in soundscapes, provides an opportunity to better understand and subsequently manage climate change. This paper focuses on the development of new spectrogram-based analysis methods to expand the possibilities of comparative analysis of soundscapes. The database to be analysed with the new methods is provided by the WikliNathi project, a long-Term monitoring study to investigate the sonic changes of populations of living organisms as well as geophone and anthropophone sounds in a nature reserve. The developed methods of analysis will be presented in detail. Selected audio recordings are analysed for changes in the sounds of great tits, grasshoppers and frogs from 2018 to 2023 using spectral flatness, temporal flatness and onset detection in aligned time-frequency regions. The evaluation of the results shows that the proposed new methods can be used to obtain more detailed and complementary results in future studies as part of this and other bioacoustic projects.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Ecoacoustics; soundscape analysis; spectral flatness measure; spectrogram-based analysis; temporal flatness measure